Malignant melanoma of the cecum and small intestine. Issue 3 (2nd July 2020) - Tan, Christopher; Yanchak, Teresa; Ramirez, Jonathan
Abstract: Malignant melanoma is the most lethal skin cancer. While it represents about 5% of all cutaneous malignancies for men and women, melanoma accounts for the most skin cancer deaths. Symptomatic gastrointestinal involvement from primary malignant cutaneous melanoma is uncommon and represents only 1% to 4% of melanoma cases but is found in 60% of autopsies in patients who have had a primary cutaneous melanoma. We present a case of metastatic melanoma in a 61-year-old man with initial symptomatic cecal melanoma and subsequent jejunal involvement discovered during endoscopy.